MEMUASKAN KONSUMEN MELALUI PENYEIMBANGAN PEMASARAN INTERNAL DAN PEMASARAN EKSTERNAL - Hari, Abdul Hadi (Kiat Bisnis, 2014)
Everyone in the organization is a consumer, and internal consumer should get service and like a job, before they can effectively serve the end consumer. A process of satisfying consumers focused exclusively on the creation of an external customer satisfaction based on competencies derived from internal marketing. Consumer satisfaction can be obtained through internal marketing mix includes; product, price, communication and distribution. Internal marketing is a holistic management process that integrates the various functions of the organization to ensure that all elements of the organization to understand its activities aimed to satisfying internal and external consumer.Keywords : Consumer, satisfaction, internal marketing